A thermally activated peracetic acid catalyst for rapid degradation of tetracycline hydrochloride wastewater and its preparation and application method
By thermally activating the composite catalyst of peracetic acid and cobalt ferrite doped with biochar, the problem of difficult removal of tetracycline in the water environment is solved, and efficient and rapid degradation effect is achieved, meeting the needs of environment and health and safety.
Patent Information
- Application Number
- CN202310630219.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-31
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-05-31
AI Technical Summary
The prior art is difficult to quickly and efficiently remove tetracycline in the water environment, resulting in environmental pollution and human health risks.
By thermally activate peracetic acid, combined with iron and cobalt-doped biochar composite catalyst, efficient degradation of tetracycline hydrochloride wastewater is achieved. The catalyst is prepared by microwave reaction and high-temperature calcination, and cobalt ferrite is uniformly distributed on the surface of biochar, enhancing catalytic activity.
Under 60°C, the catalyst can completely degrade tetracycline hydrochloride wastewater within 1 minute, with high degradation efficiency and good catalyst stability, and the leaching rate is lower than the national standard.
Smart Images

Figure CN116673032B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wastewater treatment, and relates to a catalyst for degrading tetracycline hydrochloride wastewater, and in particular to a thermally activated peracetic acid catalyst for rapidly degrading tetracycline hydrochloride wastewater, and a preparation method and application method thereof. Background Art
[0002] Tetracycline is a common antibiotic widely used in various bacterial epidemics and pathogenic microbial infections in medicine, animal husbandry and aquaculture. In the production and application of tetracycline, a large amount of wastewater containing tetracycline is generated and discharged into the environment. Long-term exposure in the environment will produce super bacteria, which are directly or indirectly toxic to organisms. In addition to causing serious environmental problems, long-term abuse of tetracycline will interfere with the body's endocrine system, disrupt normal physiological functions, and even cause some incurable diseases. Many studies have shown that tetracycline is widely present in urban water cycles and can be detected in surface water, groundwater and even drinking water treatment plants. Therefore, the rapid and efficient removal of tetracycline in the water environment is of great significance to human health and environmental ecological safety.
[0003] Peracetic acid, an emerging oxidant, is an environmentally friendly disinfectant that has been widely used in food processing, medical, chemical, papermaking and other industries. It has become a hot topic in advanced oxidation technology because of its high reduction potential, easy handling and basically no toxic by-products. Thermal activation is one of the most effective strategies to improve the efficiency of peracetic acid in removing pollutants, and it is also a new development in advanced oxidation process water treatment. The addition of heat will produce more hydroxyl radicals (·OH), organic free radicals (CH3CO(O)O·), superoxide radicals (·O 2- ) and singlet oxygen ( 1 O2) and other highly active oxidizing species. Thermal activation has the advantages of convenience and high efficiency. At present, there are very few reports on thermally activated peracetic acid. The thermally activated peracetic acid system further improves the ability of catalytic oxidation of tetracycline hydrochloride. The high response, high catalytic oxidation performance and high stability of the catalyst are the key to the present invention. The present invention improves the catalytic performance of biochar by thermally activating peracetic acid and introducing metal ions iron and cobalt, while achieving efficient removal of tetracycline wastewater. Summary of the invention
[0004] The first object of the present invention is to provide a thermally activated peracetic acid catalyst for rapid degradation of tetracycline hydrochloride wastewater;
[0005] The second object of the present invention is to provide a method for preparing a catalyst for rapidly degrading tetracycline hydrochloride wastewater by heat-activated peracetic acid;
[0006] The third object of the present invention is to provide an application method of a heat-activated peracetic acid catalyst for rapidly degrading tetracycline hydrochloride wastewater.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] (I) The present invention provides a method for preparing a catalyst for rapidly degrading tetracycline hydrochloride wastewater by heat-activated peracetic acid, comprising the following steps:
[0009] S1. Dissolving corn stalks ground into powder, sludge subjected to centrifugal drying, iron nitrate and cobalt nitrate in water, adding the mixed solution into a microwave oven for microwave reaction, and washing and drying the synthesized substances to obtain a composite catalyst precursor;
[0010] S2. The composite catalyst precursor is placed in a tubular furnace and calcined at 500° C. for 3 h in a nitrogen atmosphere. After the reaction, the synthesized material is ground and sieved to obtain a composite catalyst doped with cobalt ferrite and biochar.
[0011] Furthermore, in S1, the mass ratio of corn straw, sludge, ferric nitrate and cobalt nitrate is 3g:1g:8.08g:2.91g.
[0012] Furthermore, in S1, the microwave reaction temperature is 70°C, the microwave reaction power is 250W, and the microwave reaction time is 30min.
[0013] Furthermore, in S1, the washing method is: washing with anhydrous ethanol and deionized water alternately for 2 to 3 times.
[0014] Furthermore, in S1, the drying temperature is 60-80° C., and the drying time is 2-6 hours.
[0015] Furthermore, the effective components of the sludge are silicon dioxide, calcium oxide and calcium oxide, with mass fractions of 46.9% silicon dioxide, 9.5% calcium oxide and 3.2% calcium oxide respectively. Other components in the sludge have no impact on the present application.
[0016] (ii) The present invention also provides a thermally activated peracetic acid catalyst for rapid degradation of tetracycline hydrochloride wastewater, which is prepared according to the preparation method described above. The catalyst is an iron and cobalt-doped biochar composite catalyst, which is a composite catalyst doped with cobalt ferrite and biochar material.
[0017] (III) The present invention also provides an application method of a heat-activated peracetic acid catalyst for rapid degradation of tetracycline hydrochloride wastewater, which specifically comprises: placing the cobalt ferrite-doped biochar composite catalyst into the wastewater to be treated, stirring, and adding peracetic acid after reaching adsorption equilibrium to carry out a degradation reaction.
[0018] Furthermore, the degradation reaction temperature is 25 to 70° C., and the reaction time is 10 to 60 seconds.
[0019] Furthermore, the concentration of the cobalt ferrite-doped biochar composite catalyst in the wastewater is 0.1 g / L, and the concentration of peracetic acid in the wastewater is 0.6 mmol / L.
[0020] Furthermore, the stirring time is 10 to 30 minutes.
[0021] The beneficial effects of the present invention are:
[0022] 1. The heat-activated and highly efficient tetracycline hydrochloride wastewater degradation catalyst prepared by the present invention changes the morphology of the agglomeration of cobalt ferrite and biochar, and the cobalt ferrite is evenly distributed on the surface of the biochar, exposing more active sites, strengthening the structure of the composite catalyst, and increasing its ability to activate peracetic acid.
[0023] 2. The cobalt ferrite-doped biochar composite catalyst synthesized by the present invention has certain magnetism, which is conducive to the recovery and reuse of the composite catalyst.
[0024] 3. The heat-activated and highly efficient tetracycline hydrochloride wastewater degradation catalyst prepared by the present invention has an iron and cobalt leaching rate lower than the national wastewater discharge standard in the stability test.
[0025] 4. The synthetic material cobalt ferrite doped biochar composite catalyst of the present invention can activate peracetic acid at 60°C and completely degrade tetracycline hydrochloride-containing wastewater in only 1 minute with high degradation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of the cobalt ferrite-doped biochar composite catalyst in Example 1;
[0027] Figure 2 is the XRD pattern of the cobalt ferrite-doped biochar composite catalyst in Example 1;
[0028] Figure 3 This is the XPS graph of the cobalt ferrite-doped biochar composite catalyst in Example 1;
[0029] Figure 4 This is a diagram showing the removal effect of different reaction systems in Example 1 for efficient activation of peracetic acid for oxidative degradation of tetracycline hydrochloride;
[0030] Figure 5 This is a diagram showing the removal effect of peracetic acid at different temperatures activated by the cobalt ferrite-doped biochar composite catalyst in Example 1;
[0031] Figure 6This is a diagram showing the effect of the cobalt ferrite-doped biochar composite catalyst in Example 1 being reused for 5 times to remove tetracycline hydrochloride;
[0032] Figure 7 This is a diagram showing the effect of using the cobalt ferrite-doped biochar composite catalyst in Examples 2 to 4 to remove tetracycline hydrochloride in different water bodies. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. The experimental methods used in the following embodiments, unless otherwise specified, are all conventional methods, and the reagents, methods and equipment used, unless otherwise specified, are all conventional reagents, methods and equipment in the technical field.
[0034] Example 1
[0035] This embodiment provides a heat-activated peracetic acid catalyst for efficient degradation of tetracycline hydrochloride wastewater, which is a cobalt ferrite-doped biochar composite catalyst, and its preparation method is:
[0036] (1) 1 g of centrifugally dried sludge, 3 g of dried and ground corn stalks, 8.08 g of Fe(NO3)3·9H2O and 2.91 g of Co(NO3)2·6H2O were placed in a three-necked flask and dissolved with 50 mL of ultrapure water. The mixture was placed in a microwave oven at 70.0°C for 30 min at a power of 250.0 W. After the reaction, the mixture was taken out and cooled to room temperature. The mixture was then rinsed with deionized water and ethanol, centrifuged three times until the supernatant liquid was colorless, and then dried for 24 h to obtain the precursor.
[0037] (2) The precursor is placed in a tubular furnace under a nitrogen atmosphere and calcined at 500° C. for 3 h. After the reaction is completed, the synthesized material is ground and sieved to obtain a cobalt ferrite-doped biochar composite catalyst.
[0038] The cobalt ferrite-doped biochar composite catalyst was characterized, and the SEM, XRD and XPS images were shown in Figure 2. Figure 1-3 shown.
[0039] The above-prepared cobalt ferrite-doped biochar composite catalyst was used to test the effect of tetracycline hydrochloride wastewater treatment:
[0040] The application method is: putting the cobalt ferrite-doped biochar composite catalyst into the tetracycline hydrochloride wastewater to be treated, stirring, and adding peracetic acid to start the reaction treatment after reaching adsorption equilibrium, and the treatment time is 10 to 60 seconds.
[0041] Comparison of application with control group:
[0042] Experimental group 1: peracetic acid and cobalt ferrite-doped biochar composite catalyst (PAA / CFB-2 group, CFB-2: 0.1 g / L, PAA: 0.6 mmol / L, TC: 10 mg / L) were present in the system;
[0043] Experimental group 2: peracetic acid and cobalt ferrite combined with biochar composite catalyst in the 60℃ system (60℃ / PAA / CFB-2 group, 60℃, PAA: 0.6mmol / L, CFB-2: 0.1g / L, TC: 10mg / L);
[0044] Control group 1: only the oxidant peracetic acid (PAA group, 0.6mmol / L, TC: 10mg / L) was added to the system;
[0045] Control group 2: peracetic acid and biochar catalyst were present in the system (PAA / BC group, BC: 0.1 g / L, PAA: 0.6 mmol / L, TC: 10 mg / L);
[0046] Control group 3: temperature only (60℃ group, TC: 10mg / L);
[0047] Control group 4: only peracetic acid was added to the 60℃ system (60℃ / PAA group, 60℃, PAA: 0.6mmol / L, TC: 10mg / L);
[0048] Control group 5: Peracetic acid and biochar catalyst were present in the 60℃ system (60℃ / PAA / BC group, 60℃, PAA: 0.6mmol / L, BC: 0.1g / L, TC: 10mg / L).
[0049] Among them, in the control group, the biochar preparation method is as follows: 1g of sludge after centrifugal drying and 3g of corn straw that was dried and ground into powder were taken in a tubular furnace under nitrogen atmosphere and calcined at 500℃ for 3h. After the reaction was completed, the mixture was cooled to room temperature and submerged and sieved to obtain the biochar catalyst.
[0050] The above application method was used to treat a 10 mg / L tetracycline hydrochloride solution (wastewater to be treated). After reacting for 1 minute, the solution was filtered with a 0.22 μm filter membrane and then tested with a UV-visible spectrophotometer for the remaining tetracycline hydrochloride concentration. Different reaction systems had different effects on removing tetracycline hydrochloride. The results are shown in Figure 2. Figure 4As shown, the PAA / CFB-2 group and the 60°C / PAA / CFB-2 group have better acid tetracycline removal capabilities, and compared with the two, the 60°C / PAA / CFB-2 group completely removes tetracycline hydrochloride, indicating that the cobalt ferrite-doped biochar composite catalyst prepared in this embodiment has an outstanding tetracycline hydrochloride removal effect at a temperature of 60°C.
[0051] The removal effects of 10 mg / L tetracycline hydrochloride in different water bodies - ultrapure water, deionized water, tap water and Nenjiang water in a system of peracetic acid (0.6 mmol / L) activated by cobalt ferrite-doped biochar composite catalyst (0.1 g / L) were compared. The results showed that after 1 minute of reaction, tetracycline hydrochloride in different water bodies had a good removal effect.
[0052] The removal effects of 10 mg / L tetracycline hydrochloride wastewater in the system of peracetic acid (0.6 mmol / L) activated by cobalt ferrite-doped biochar composite catalyst (0.1 g / L) at different temperatures were compared. The results showed that after 1 min of reaction, tetracycline hydrochloride had a good removal effect when the temperature was in the range of 50 to 70 degrees. Figure 5 shown.
[0053] Stability test of cobalt ferrite doped biochar composite catalyst: The cobalt ferrite doped biochar composite material was placed in 100mL 10mg / L tetracycline hydrochloride solution for degradation experiment, and the cobalt ferrite doped biochar composite catalyst was recovered for regeneration, and the degradation experiment was continued. After repeating 5 times, the removal effect of tetracycline hydrochloride was still above 75%. Figure 6 shown.
[0054] Example 2
[0055] This embodiment provides a heat-activated peracetic acid catalyst for efficient degradation of tetracycline hydrochloride wastewater, which is a cobalt ferrite-doped biochar composite catalyst, and its preparation method is:
[0056] (1) 1 g of centrifugally dried sludge, 3 g of dried and ground corn stalks, 8.08 g of Fe(NO3)3·9H2O and 2.91 g of Co(NO3)2·6H2O were placed in a three-necked flask and dissolved with 50 mL of ultrapure water. The mixture was placed in a microwave oven at 70.0°C for 30 min at a power of 250.0 W. After the reaction, the mixture was taken out and cooled to room temperature. The mixture was then rinsed with deionized water and ethanol, centrifuged three times until the supernatant liquid was colorless, and then dried for 24 h to obtain the precursor.
[0057] (2) The precursor is placed in a tubular furnace under a nitrogen atmosphere and calcined at 500° C. for 3 h. After the reaction is completed, the synthesized material is ground and sieved to obtain a cobalt ferrite-doped biochar composite catalyst.
[0058] The cobalt ferrite-doped biochar composite catalyst prepared in this example was used to treat tetracycline hydrochloride wastewater:
[0059] The application method is as follows: take 100mL of 10mg / L tetracycline hydrochloride solution, add 0.1g / L catalyst, place the mixed wastewater on a heatable magnetic stirrer at a speed of 450rpm, and stir at room temperature for 30min to reach adsorption equilibrium; then start to heat up, and when the temperature reaches 60°C, add 0.6mmol / L peracetic acid to start the degradation reaction, take 5mL of samples at 10, 20, 30, 40, 50, and 60s, filter with a 0.22μm filter membrane, and measure the residual concentration of tetracycline hydrochloride with a UV-visible spectrophotometer at a wavelength of λ=360nm. After 1 minute of reaction, the degradation rate of tetracycline hydrochloride by the cobalt ferrite-doped biochar composite catalyst reaches 95.9%.
[0060] Example 3
[0061] This embodiment provides a heat-activated peracetic acid catalyst for efficient degradation of tetracycline hydrochloride wastewater, which is a cobalt ferrite-doped biochar composite catalyst, and its preparation method is:
[0062] (1) 1 g of centrifugally dried sludge, 3 g of dried and ground corn stalks, 8.08 g of Fe(NO3)3·9H2O and 2.91 g of Co(NO3)2·6H2O were placed in a three-necked flask and dissolved with 50 mL of ultrapure water. The mixture was placed in a microwave oven at 70.0°C for 30 min at a power of 250.0 W. After the reaction, the mixture was taken out and cooled to room temperature. The mixture was then rinsed with deionized water and ethanol, centrifuged three times until the supernatant liquid was colorless, and then dried for 24 h to obtain the precursor.
[0063] (2) The precursor is placed in a tubular furnace under a nitrogen atmosphere and calcined at 500° C. for 3 h. After the reaction is completed, the synthesized material is ground and sieved to obtain a cobalt ferrite-doped biochar composite catalyst.
[0064] The cobalt ferrite-doped biochar composite catalyst prepared in this example was used to treat tetracycline hydrochloride wastewater:
[0065] The application method is as follows: prepare tetracycline hydrochloride solution with 100 mL of 10 mg / L tap water, add 0.1 g / L of catalyst, place the mixed wastewater on a heatable magnetic stirrer at a speed of 450 rpm, and stir at room temperature for 30 min to reach adsorption equilibrium; then start to heat up, and when the temperature reaches 65°C, add 0.6 mmol / L of peracetic acid to start the degradation reaction, take 5 mL of samples at 10, 20, 30, 40, 50, and 60 s, filter with a 0.22 μm filter membrane, and measure the residual concentration of tetracycline hydrochloride with a UV-visible spectrophotometer at a wavelength of λ=360 nm. After 1 minute of reaction, the degradation rate of tetracycline hydrochloride by the cobalt ferrite-doped biochar composite catalyst reaches 94.0%.
[0066] Example 4
[0067] This embodiment provides a heat-activated peracetic acid catalyst for efficient degradation of tetracycline hydrochloride wastewater, which is a cobalt ferrite-doped biochar composite catalyst, and its preparation method is:
[0068] (1) 1 g of centrifugally dried sludge, 3 g of dried and ground corn stalks, 8.08 g of Fe(NO3)3·9H2O and 2.91 g of Co(NO3)2·6H2O were placed in a three-necked flask and dissolved with 50 mL of ultrapure water. The mixture was placed in a microwave oven at 70.0°C for 30 min at a power of 250.0 W. After the reaction, the mixture was taken out and cooled to room temperature. The mixture was then rinsed with deionized water and ethanol, centrifuged three times until the supernatant liquid was colorless, and then dried for 24 h to obtain the precursor.
[0069] (2) The precursor is placed in a tubular furnace under a nitrogen atmosphere and calcined at 500° C. for 3 h. After the reaction is completed, the synthesized material is ground and sieved to obtain a cobalt ferrite-doped biochar composite catalyst.
[0070] The cobalt ferrite-doped biochar composite catalyst prepared in this example was used to treat tetracycline hydrochloride wastewater:
[0071] The application method is as follows: 100 mL of 10 mg / L river water is prepared into a tetracycline hydrochloride solution, 0.1 g / L of catalyst is added, the mixed wastewater is placed on a heatable magnetic stirrer, the rotation speed is 450 rpm, and the mixture is stirred at room temperature for 30 min to reach adsorption equilibrium; then the temperature is raised, and when the temperature reaches 70°C, 0.6 mmol / L of peracetic acid is added to start the degradation reaction, 5 mL of samples are taken at 10, 20, 30, 40, 50, and 60 s, and the residual concentration of tetracycline hydrochloride is measured at a wavelength of λ=360 nm by a UV-visible spectrophotometer after filtering with a 0.22 μm filter membrane. After 1 minute of reaction, the degradation rate of tetracycline hydrochloride by the cobalt ferrite-doped biochar composite catalyst reaches 93.04%. Figure 7 shown.
[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present invention, and such modifications or equivalent substitutions should also be deemed to fall within the protection scope of the technical solution of the present invention.
Claims
1. Application of thermally activated peracetic acid as a catalyst for rapid degradation of tetracycline hydrochloride wastewater, characterized in that: The application method is as follows: put the cobalt ferrite-doped biochar composite catalyst into the tetracycline hydrochloride wastewater to be treated, stir, and add peracetic acid after reaching adsorption equilibrium to carry out degradation reaction; the degradation reaction temperature is 50~70ºC, and the reaction time is 10~60s; The preparation method of the cobalt ferrite-doped biochar composite catalyst comprises the following steps: S1. Dissolving corn stalks ground into powder, sludge subjected to centrifugal drying, iron nitrate and cobalt nitrate in water, adding the mixed solution into a microwave oven for microwave reaction, and washing and drying the synthesized substances to obtain a composite catalyst precursor; S2. The composite catalyst precursor was placed in a tubular furnace and calcined at 500°C for 3 h under a nitrogen atmosphere. After the reaction, the synthesized material was ground and sieved to obtain a composite catalyst doped with biochar and cobalt ferrite.
2. The use of the heat-activated peracetic acid catalyst for rapid degradation of tetracycline hydrochloride wastewater according to claim 1, characterized in that: In the S1, the mass ratio of corn straw, sludge, ferric nitrate and cobalt nitrate is 3 g:1 g:8.08 g:2.91 g.
3. The use of the thermally activated peracetic acid catalyst for rapid degradation of tetracycline hydrochloride wastewater according to claim 1, characterized in that: In S1, the microwave reaction temperature is 70°C, the microwave reaction power is 250 W, and the microwave reaction time is 30 min.
4. The use of the heat-activated peracetic acid catalyst for rapid degradation of tetracycline hydrochloride wastewater according to claim 1, characterized in that: In S1, the washing method is: washing with anhydrous ethanol and deionized water alternately 2 to 3 times.
5. The use of the heat-activated peracetic acid catalyst for rapid degradation of tetracycline hydrochloride wastewater according to claim 1, characterized in that: In S1, the drying temperature is 60-80°C and the drying time is 2-6 h.
6. The use of the thermally activated peracetic acid catalyst for rapid degradation of tetracycline hydrochloride wastewater according to claim 1, characterized in that: The concentration of the cobalt ferrite-doped biochar composite catalyst in tetracycline hydrochloride wastewater is 0.1 g / L, and the concentration of peracetic acid in the wastewater is 0.6 mmol / L.
7. The use of the thermally activated peracetic acid catalyst for rapid degradation of tetracycline hydrochloride wastewater according to claim 1, characterized in that: The stirring time is 10 to 30 min.